Isolation and Identification of Parasites from Lactuca Sativa. - Hadi, Afkar M (Al-Nahrain Journal of Science, 2018)
This investigation was designed to determine the occurrence of intestinal parasites in Lactuca sativa from November 2008 to April 2009 from Baghdad markets as a primary effort in Iraq. Twelve genera and species of intestinal parasites appear in lactuca were as follow: Toxocara canis 53.3%, Echinococcus sp. 41.6%, Hymenolepis sp. 26.6%, Ascaris lumbricoides 20%, Anoplocephala sp.15%, Strongyloides stercoralis 15%, Parascaris equorum 13.3%, Taenia sp.11.6%, Toxocara vitulorum 8.3%, Strongyloides westeri 6.6%, Ancylostoma duodenale 5%, Stongylus sp.5%. Unfortunately, the scarcity of fresh water has meant that urban gardeners are increasingly irrigating their plots with wastewater. This poses a threat to public health. The high rate of eggs in lactuca was recoded at April 60% temperatures between (30- 31c◦) that mean this Optimum Temperatures for eggs; the law rate off eggs at January 13.3% temperature between (1-10c◦); low temperatures inhibit complete development of the cells inside the eggs.